Pengaruh Ekspor, Impor, Dan Kurs Terhadap Neraca Pembayaran Negara Asean Perspektif Ekonomi Islam - Mutiara Aziziah; Erike Anggraeni; Zathu Restie Utamie (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2026)
This study aims to analyze the effect of exports, imports, and exchange rates on the balance of payments in five ASEAN countries, namely Indonesia, Malaysia, Singapore, Thailand, and Brunei Darussalam during the 2014–2024 period from both economic and Islamic perspectives. This research employs a quantitative associative approach using panel data obtained from the World Bank through the World Development Indicators database. The data were analyzed using panel data regression with EViews software. The findings reveal that exports have a positive and significant effect on the balance of payments by increasing foreign exchange earnings and strengthening the current account. Imports also significantly affect the balance of payments, particularly when they consist of capital goods and raw materials that support domestic production and economic growth, although excessive imports of consumption goods may weaken external balances. Furthermore, the exchange rate significantly influences the balance of payments through its impact on export competitiveness and import costs. Simultaneously, exports, imports, and exchange rates significantly affect the balance of payments in the five ASEAN countries. From an Islamic economics perspective, balance of payments management should uphold the principles of balance (tawazun), justice (‘adl), and the avoidance of riba and speculative activities in international economic transactions. The study contributes to the literature by integrating macroeconomic analysis with Islamic economic principles in the ASEAN context.